Prevalence of malnutrition among Portuguese elderly living in nursing homes : preliminary results of the PEN-3S project - Madeira, Teresa (2020)
Proceedings of the 3rd IPLeiria’s International Health Congress Leiria, Portugal. 6-7 May 2016